THE IMPACT OF PUBLIC-PRIVATE PARTNERSHIPS ON THE QUALITY OF PUBLIC SERVICES (REMUNOM, 2024)
This paper analyzes the impact of Public-Private Partnerships (PPPs) on the quality of public services, focusing on their application in essential sectors such as infrastructure, health and education. PPPs are presented as an efficient model for implementing large-scale public projects, making it possible to combine the resources and expertise of the private sector with the objectives and needs of the public sector. Using a theoretical framework based on Alexandrino and Paulo (2016), Cabral and Lazzarini (2010), Martins (2015), Harmmani (2006), the study explores examples of PPPs in Brazil, such as Line 4-Yellow of the São Paulo Metro, demonstrating the benefits of these partnerships in terms of innovation, modernization and improvements in the provision of services to the population. The main challenges in implementing PPPs are also discussed, including transparency, cost control and maintaining the quality of services. To address these challenges, the paper proposes best practices, such as drawing up clear contracts, rigorous supervision and long-term strategic planning. It concludes that, when well-managed, PPPs can have a significant positive impact on the quality of public services, promoting efficiency, innovation and sustainable social development.